Монголын нууц товчоон дахь “ Хоч нэр”-ийн тухай: About Nicknames in secret history of Mongolia - Жигмэддорж, Э. (Acta Mongolica, 2005)
The contest of nicknames and their meanings and person’s name was arisen from clan’s names in the secret history is proved the traditional giving nicknames among Mongolian people from ancient time. Ancient Mongolian person’s names and clan’s names were meant his position of social, character, appearance and origin, territory, nomadic way of life and special feature from others.